Parental involvement in early care in Neonatal Intensive Care Units: A systematic literature review (Research, Society and Development, 2024)
The article aims to analyze studies on family-centered care in early intervention in premature babies, emphasizing parental involvement, with a focus on the context in Portugal. Globally, 15 million babies are born prematurely annually, with a rate of approximately 8% in Portugal. Over the last five decades, premature birth rates have increased while infant mortality has decreased, indicating advancements in obstetric and neonatal care. Premature newborns face significant risks, including developmental delays, sensory deficits, learning difficulties, and cerebral palsy. Early interventions are essential to refer these children to services that promote their development during periods of maximum neuronal plasticity. Early Intervention (EI) has shown promising results improving developmental outcomes and reducing biological and social risk fator´s impact. However, there is a shortage of national research on this topic. This study reviewed articles from 2015 to 2022, identifying 17 that addressed premature newborns, early intervention, and family care, evaluating the quality of clinical trials with PEDro Assessment Scale. The article emphasizes the importance of early intervention and family care for the development of premature babies and their families, highlighting the need for more national research in this area. Promoting additional studies can enhance understanding and improve care for this vulnerable population.